Telehealth in Brazil: a scoping review - Cezário, Laís Renata Almeida (2024)
This scoping review discusses the development of telehealth in Brazil from its implementation by the Brasil Redes National Telehealth Program in 2007 and expansion based on scientific publications on the topic indexed on the Medical Literature Analysis and Retrieval System Online (Medline), Latin American and Caribbean Health Sciences Literature (Lilacs) and Scientific Electronic Library Online (SciELO) from 2007 to 2022. A total of 177 studies were included, mostly published in 2021 and 2020. Telehealth actions were conducted especially in Southeastern and Southern Brazil, mostly by telediagnosis and teleconsultation. Telehealth actions were most frequent in medicine (54.80%), mainly focused on General Health and cardiology (38.42% and 19.21%, respectively). Telehealth in Brazil has advanced, especially after the COVID-19 pandemic, as it triggered the need to expand these services. Southeastern and Southern Brazil have offered the largest number of services, with telediagnosis and teleconsultation in primary care being the most frequent.